Structural rationalisation of co-crystals formed between trithiocyanuric acid and molecules containing hydrogen bonding functionality - Ahn, Sung-Hoon; PrakashaReddy, J.; Kariuki, B. M.; Chatterjee, S.; Ranganathan, A.; Pedireddi, V. R.; Rao, C. N. R.; Harris, Kenneth D. M. (Chemistry - A European Journal, 2005)
Crystallisation of trithiocyanuric acid (TTCA) from various organic solvents that have hydrogen bonding capability (acetone, 2-butanone, dimethylformamide, dimethyl sulfoxide, methanol and acetonitrile) leads to the formation of co-crystals in which the solvent molecules are incorporated together with TTCA in the crystal structure. Structure determination by single-crystal X-ray diffraction reveals that these co-crystals can be classified into different groups depending upon the topological arrangement of the TTCA molecules in the crystal structure. Thus, three different types of single-tape arrangements of TTCA molecules and one type of double-tape arrangement of TTCA molecules are identified. In all co-crystals, hydrogen-bonding interactions are formed through the involvement of N-H bonds of TTCA molecules in these tapes and the other molecule in the co-crystal. Detailed rationalisation of the structural properties of these co-crystals is presented.
Keywords: crystal engineering; hydrogen bonds; nitrogen heterocycles; structure elucidation

Overview on the cellulose based conducting composites - Pandey, Jitendra Kumar; Takagi, Hitoshi; Nakagaito, Antonio Norio; Saini, Daulat Ram; Ahn, Sung-Hoon (Composites Part B-Engineering, 2012)
Biopolymer based composites have been employed in numerous applications with increasing interest not only due to renewable, eco-friendly nature, but also because of the flexibility in processing conditions and competitive cost of their end products. The conductive materials from biopolymers have been found applicable in robots, medical imaging, sensitive membranes, actuators, visual displays, electronic wiring and shielding, and components in batteries. Cellulose is one of the most abundant biopolymers in the nature, which has received special attention for development of conducting materials due to biocompatibility for protein and drug immobilization and ability to form the composites with synthetic polymers. The present review is aimed to provide concisely the current status in this field of conducting composites from cellulose, with brief discussions of associated problems and future applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fibres; mechanical properties; Nano-structures; Polymer-matrix composites (PMCs)